EFFECT OF CONTEXTUAL TEACHING AND LEARNING ON IMPROVING ABILITY OF MATHEMATICAL COMMUNICATIONS VIEWED FROM INTEREST LEVEL OF STUDENT LEARNING - Hoer Mutaqin; Jejen Abdul Fatah; Nurkolis Nurkolis; Asep Ikin Sugandi; Wahyudin Wahyudin ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study aims to obtain a picture of improving the ability of mathematical communication on the implementation of learning contextual teaching and learning approach viewed from the level of student learning interest. The method used in this research is an experiment with factorial design 3 x 2. The population is all junior high school students in Karawang regency with the subject of the sample is two classes of X in one of SMP Negeri in Kabupaten Karawang. The first class gets learning with contextual teaching and learning, and the second class gets learning by direct learning. From the research, it can be concluded that there are differences in the mathematical communication ability of the students whose learning using Contextual Teaching and Learning learning with direct learning, there is no difference in the improvement of mathematical communication ability among students who have high, medium and low learning interest, there is an interaction between the learning approach and the level interest in learning to improve the ability of mathematical communication, the implementation of learning using Contextual Teaching and Learning learning has been running with the steps that have been determined, the students' difficulties in completing the problem of understanding and mathematical communication lies in the indicator (a) linking a concept/principle with the concept/principle (b) can apply formulas in simple calculations and work on algorithmic calculations, (c) associate a concept/principle with other concepts/principles.